Effect Of Combination of Wheat Flour with Yellow Pumpkin Paste and Yeast Concentration on The Quality of Yellow Pumpkin Donuts (Cucurbita Moschata) - Novi Mailidarni; Jauhari Jauhari (Universitas Teuku Umar, 2023)
The aim of this research was to determine the effect of the ratio of pumpkin paste and yeast concentration on donuts. The variables used include the effect of the ratio of wheat flour to pumpkin pasta and the concentration of yeast on the quality of pumpkin donuts, the ratio of 40% pumpkin paste: 60% wheat flour, 50% pumpkin pasta: 50% wheat flour, 60% pumpkin pasta: 40% and pumpkin paste 1%, 2% and 3% respectively. Meanwhile, the parameters explained are water content, ash content, and organoleptic tests (color, taste, aroma and texture). The research data were processed using a Factorial Completely Randomized Design (CRD) with 2 replications, data analysis using ANOVA and the Least Significant Difference Follow-up Test (BNT).The best treatment in this study was the T2L2 treatment and the SNI 01-2000 donut quality requirements were 50% pumpkin pasta donuts with a wheat flour ratio of 50: 50% (T2) and a yeast concentration of 2% (L2) with a water content value of 20.71%. , ash content value 0.91%, organoleptic test color value 3.37%, taste value 3.83%, aroma value 3.37% and texture value 3.54%.